Acquired C1 esterase inhibitor deficiency or serendipity? The chance finding of a paraprotein after an apparently low C1 esterase inhibitor concentration. Issue 4 (26th March 2004) - Sinclair, D; Smith, A; Cranfield, T; Lock, R J
Abstract : Acquired C1 esterase inhibitor deficiency is a rare condition, usually presenting after the 2nd decade of life, and is often related to underlying conditions such as autoimmune and lymphoproliferative disorders. This case report describes a man whose initial clinical presentation with acute angioedema and whose initial estimation of a low C1 esterase inhibitor concentration indicated that he had an acquired angioedema, possibly secondary to a B cell neoplasm. A paraprotein was detected, and although its detection was serendipitous because it hinged on a spurious C1 esterase inhibitor result, this case confirms the role of C4 concentrations in the investigation of C1 esterase inhibitor deficiency. It also confirms the need to obtain repeat confirmatory samples before arriving at a diagnosis, however convincing the clinical signs may be.